PENDAMPINGAN SEKOLAH MINGGU DAN PENGEMBANGAN KEPEMIMPINAN ANAK DI KIDS CHURCH GBI TABGHA BOTANIA 2 BATAM - Simanjuntak, Paulus Bernard Hasiholan; Purba, Gomgom; Situmorang, Maruba; Hutabarat, Jessica Janet (Unit Penelitian dan Pengabdian Kepada Masyarakat, 2024)
Abstract The purpose of this community service is to socialize and implement Sunday school mentoring and children's leadership development at Kids Church GBI Tabgha Botania 2 Batam. This community service uses the methodology used in this study is a qualitative approach with descriptive analysis. Data were collected through literature studies from various sources, including books, journal articles, and relevant community service reports. In addition, interviews with Sunday school children and Sunday school teachers were conducted to obtain direct perspectives on Sunday school mentoring and children's leadership development. The results of Sunday school mentoring and children's leadership development at Kids Church GBI Tabgha Botania 2 Batam are that Sunday School provides a platform for children to learn to collaborate and work together in teams. Children who are involved in group activities at Sunday School are able to develop better communication skills, which is an important aspect of leadership. The teaching methods applied in Sunday School also contribute to the development of children's leadership. This method not only increases a sense of responsibility, but also teaches children about the importance of planning and organizing two very important skills in leadership. Keywords: Mentoring, Sunday school, children's leadership